Tuning Areal Density and Surface Passivation of ZnO Nanowire Array Enable Efficient PbS QDs Solar Cells with Enhanced Current Density. Issue 1 (18th November 2019) - Tavakoli Dastjerdi, Hadi; Prochowicz, Daniel; Yadav, Pankaj; Tavakoli, Mohammad Mahdi
Abstract: Colloidal PbS quantum dots (QDs) have provoked a revolution in the field of optoelectronic devices owing to their low‐cost fabrication processing and excellent physical properties. Recently, the fabrication of nanostructured PbS QD photovoltaic (PV) devices based on zinc oxide (ZnO) nanowire array appears as an effective strategy for improving the overall device performance. Despite its potentially strong impact on the device performance, the role of nanowire areal density on photon absorption and exciton dynamics has not yet been studied and still remains unexplored. Here, for the first time, the areal density of ZnO nanowires is tuned through controlling the precursor concentration and its impact on PbS QD PV performance is studied. It is found that the device with optimized ZnO nanowire areal density yields significantly increased power conversion efficiency (PCE) (10.1% vs 8.5% of control nanowire‐based device) due to improved antireflection effect and reduced surface recombination states. To further improve the photovoltaic performance, the ZnO nanowire surface is treated with hydrogen plasma. Transient photovoltage (TPV) measurement reveals that this passivation process noticeably reduces the nonradiative charge recombination yielding a champion device with a remarkable PCE of 10.8%. Abstract : Remarkably enhanced photovoltaic (PV) performance for PbS quantum dot PVs is achieved through tuning the areal density of ZnO nanowire arrays, due to noticeably improved optical absorption and significant reduction of nonradiative recombination. Furthermore, surface passivation of ZnO nanowire array by hydrogen plasma results in improved power conversion efficiency from 10.1% to 10.8%.